EXAMINING INDONESIAN EFL STUDENTS’ ACCEPTANCE OF CHATGPT AS A SUPPLEMENTARY ENGLISH GRAMMAR LEARNING RESOURCE - Taufik Akbar Azwar; Fernandita Gusweni Jayanti (Wiralodra English Journal, 2025)
As Artificial Intelligence (AI) becomes increasingly prominent in multiple domains, including education, the scrutiny of the acceptance of this technology is critical for future educational agendas. ChatGPT is an example of AI that garners attention in the English Language Teaching (ELT) domain. This present study sought to evaluate English as a Foreign Language (EFL) students’ acceptance of the pedagogical implementation of ChatGPT as an English grammar learning resource in classrooms. To this end, a descriptive quantitative design was employed. A questionnaire rooted in the Technology Acceptance Model (TAM) was adapted to investigate 98 middle school students’ technological acceptance of ChatGPT upon completing a 6-week language teaching. Several items under the concern construct were added to the questionnaire to explore students’ concerns about using ChatGPT. The results suggest that the students generally had a constructive view of the usefulness, ease of use, attitude, and continuance intention to leverage ChatGPT to learn English grammar. However, some students raised concerns, such as becoming excessively reliant on ChatGPT, receiving inaccurate responses, deteriorating advanced cognitive skills, and possible academic misconduct. For pedagogical implications, this study underscores the significance of systematic instructional preparation, curricular alignment, and guidelines from educational institutions to incorporate ChatGPT into ELT classrooms